New consumers and ways of commercialization: the emerging trend - Willig, Franciele Taís (2024)
The COVID-19 pandemic has brought about changes in the economy, as lockdown and social distancing have driven a new economic sector: e-commerce, including delivery apps. This sector had been growing steadily in Brazil, especially among Generation Z, which is also part of the 4.0 consumer group. To determine how these consumers are affecting the use of delivery apps and their relationship with Generation Z, a descriptive study was conducted with a bibliographic survey of documents published between 2008 and 2022. Research carried out by the QualiBest Institute showed that in 2018, 81% of those interviewed used delivery apps, and by 2020, this number had risen to 92%. In addition, the most used application was iFood, with 86%, followed by Uber Eats, with 43% and in last place was 99 Food with 11%. Another survey carried out by the Brazilian Society of Retail and Consumption (SBVC) showed that 15% of young people from Generation Z shop exclusively online with the marketplace being the most used form, corresponding to 76%, followed by delivery apps, accounting for around 53%.